Transient Variability of the Miocene Antarctic Ice Sheet Smaller Than Equilibrium Differences. Issue 8 (16th April 2019) - Stap, L. B.; Sutter, J.; Knorr, G.; Stärz, M.; Lohmann, G.
Abstract: During the early to mid‐Miocene, benthic δ 18 O records indicate large ice volume fluctuations of the Antarctic ice sheet (AIS) on multiple timescales. Hitherto, research has mainly focused on how CO2 and insolation changes control an equilibrated AIS. However, transient AIS dynamics remain largely unexplored. Here, we study Miocene AIS variability, using an ice sheet‐shelf model forced by climate model output with various CO2 levels and orbital conditions. Besides equilibrium simulations, we conduct transient experiments, gradually changing the forcing climate state over time. We show that transient AIS variability is substantially smaller than equilibrium differences. This reduces the contribution of the AIS to δ 18 O fluctuations by more than two thirds on a 40‐kyr timescale, hence requiring a larger contribution by deep‐sea‐temperature variability. The growth rates are much slower than the decay rates, which ensures variability around a preferred small state. Finally, if the bedrock topography enlarges the West Antarctic land surface, AIS self‐sustenance increases. Key Points: The contribution of transient Antarctic ice sheet variations to Miocene δ 18 O signals is smaller than indicated by equilibrium differences Transient ice volume variability is centered around a preferred small state and is dependent on the timescale of the forcing Enlarging the West Antarctic land surface increases the self‐sustenance of the Miocene Antarctic ice sheet, decreasing the variability